1996
DOI: 10.1016/s0009-9236(96)90202-7
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and pharmacodynamic profiles of sumatriptan in migraine patients with headache recurrence or no response*

Abstract: Headache recurrence and lack of headache relief after sumatriptan do not appear to be explained by pharmacokinetic or pharmacodynamic differences between patients, which may be an important finding for the development of novel antimigraine drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 21 publications
0
33
0
Order By: Relevance
“…In short, recurrence probably cannot be uniformly attributed to any one pharmacokinetic or pharmacodynamic factor. Supporting this supposition are the findings of Visser et al [26] who reported that no differences were seen in the pharmacokinetic and pharmacodynamic profiles of patients that experienced recurrence compared with those that did not after treatment with subcutaneous sumatriptan. In this study, the investigators administered a single 6-mg subcutaneous dose of sumatriptan to 37 migraineurs at a time when they did not have a migraine.…”
Section: Opinion Statementmentioning
confidence: 83%
See 1 more Smart Citation
“…In short, recurrence probably cannot be uniformly attributed to any one pharmacokinetic or pharmacodynamic factor. Supporting this supposition are the findings of Visser et al [26] who reported that no differences were seen in the pharmacokinetic and pharmacodynamic profiles of patients that experienced recurrence compared with those that did not after treatment with subcutaneous sumatriptan. In this study, the investigators administered a single 6-mg subcutaneous dose of sumatriptan to 37 migraineurs at a time when they did not have a migraine.…”
Section: Opinion Statementmentioning
confidence: 83%
“…Factors influencing recurrence Several factors thought to play a role in headache recurrence, including patient age, duration of disease, duration of attack, severity of attack, and route of drug administration, have been examined (Table 4) [1,17,[25][26][27]. Age is thought to be a factor because adolescent migraineurs rarely report recurrence.…”
Section: Opinion Statementmentioning
confidence: 99%
“…However, response to treatment is difficult to define, in view of the variability of individual responses to any pharmacologic treatments in migraineurs, representing a troublesome obstacle for general interpretation. In the absence of encoding definition criteria for responders and non-responders to triptans in the literature, we have chosen the definition of response as at least 4 successful treatments with 10 mg rizatriptan in five attacks [1,16], as it has proved the most reliable to date.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, up to 15% of migraineurs fail to respond to triptans. As multiple clinical and genetic factors may contribute towards inter-patient difference in the clinical response to drugs, several studies have been performed to characterise the response and non-response to triptans [1].…”
Section: Introductionmentioning
confidence: 99%
“…Negative side effects of such medicines may include sedation, dry eyes, blurred vision, constipation, hypotension, photosensitivity, dizziness, vertigo, dermatological tingling, burning sensations, sinus tachycardia, intermittent claudication, myocardial infarction, nausea, vomiting, abdominal pain, diarrhea, polydipsia, and myalgia. [5][6][7][8][9][10][11] Side effects of chiropractic manipulation may include neck soreness and stiffness. A randomized study comparing effects of manipulation, medication, or both treatments.…”
Section: Introductionmentioning
confidence: 99%